2005
DOI: 10.1152/jn.00571.2004
|View full text |Cite
|
Sign up to set email alerts
|

Tilt Aftereffect and Adaptation-Induced Changes in Orientation Tuning in Visual Cortex

Abstract: The tilt aftereffect (TAE) is a visual illusion in which prolonged adaptation to an oriented stimulus causes shifts in subsequent perceived orientations. Historically, neural models of the TAE have explained it as the outcome of response suppression of neurons tuned to the adapting orientation. Recent physiological studies of neurons in primary visual cortex (V1) have confirmed that such response suppression exists. However, it was also found that the preferred orientations of neurons shift away from the adapt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
113
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(127 citation statements)
references
References 37 publications
13
113
0
1
Order By: Relevance
“…The effects of adaptation on neuronal responses are of interest, in part, because their strong perceptual consequences offer a powerful tool for understanding the physiological basis of perception (Jin et al 2005;Kohn andMovshon 2003, 2004;Krekelberg et al 2006b). In addition, adaptation is frequently used in imaging studies to probe the selectivity of cortical areas, making an understanding of its effects on neurons critical for relating these measurements to the underlying neurophysiology (Grill-Spector and Malach 2001;Krekelberg et al 2006a).…”
mentioning
confidence: 99%
“…The effects of adaptation on neuronal responses are of interest, in part, because their strong perceptual consequences offer a powerful tool for understanding the physiological basis of perception (Jin et al 2005;Kohn andMovshon 2003, 2004;Krekelberg et al 2006b). In addition, adaptation is frequently used in imaging studies to probe the selectivity of cortical areas, making an understanding of its effects on neurons critical for relating these measurements to the underlying neurophysiology (Grill-Spector and Malach 2001;Krekelberg et al 2006a).…”
mentioning
confidence: 99%
“…In neurophysiology, the TI is believed to be based on the known center-surround properties of neurons in early cortical areas and perhaps higher-level involvement [5] , while for the TAE, it is usually supposed that adaptation leads to the suppression of neuronal responses near the adapting orientation [6,7] . However, the recent study by Wissig and Kohn showed that adaptation not only causes stimulusspecifi c suppression of responsivity and repulsive shifts in tuning preference, but also leads to response facilitation and shifts in tuning toward the adapter [8] .…”
Section: Introductionmentioning
confidence: 99%
“…If the adaptor is presented to only one eye, and the test only to the other, the inter-ocular tilt aftereffect is as large (Campbell & Maffei, 1971) or almost as large (Gibson, 1937;Movshon, Chambers, & Blakemore, 1972;Paradiso et al, 1989) as that measured when both stimuli are presented to the same eye. This combination of observations suggests that tilt aftereffects are mediated by a neural substrate containing orientation and spatial-frequency selective neurons, sensitive to input from both eyes, with spatially restricted receptive fields, most likely in primary visual cortical area V1 (Campbell & Maffei, 1971;Dragoi, Sharma, & Sur, 2000;Hubel & Wiesel, 1962;Jin, Dragoi, Sur, & Seung, 2005).…”
Section: Adaptation To Orientationmentioning
confidence: 94%
“…For example, when adapting and test shapes overlap, any observed effect could be strongly impacted by contour repulsion or tilt aftereffects, likely produced in primary visual cortex rather than later shape-specific stages of processing (Dragoi et al, 2000;Jin et al, 2005). To overcome this we used an adapting stimulus that was intermittently re-positioned about the physical test location, such that the external contours of the adaptor traced a symmetrical outline about the test location (see Figure 3c).…”
Section: C)mentioning
confidence: 99%
See 1 more Smart Citation